Measuring Student Learning in Library Information Literacy Instruction Programs - Williams, Elizabeth M. (Qualitative and Quantitative Methods in Libraries, 2017)
Librarians play numerous roles in a mushrooming world of information. In academic libraries, they answer questions, manage collections of books and periodicals, and daily assist students and faculty to find information on every imaginable topic. One of their primary goals is to assess the effectiveness of the library’s instruction program by using both qualitative and quantitative measurement tools to validate the need for student information literacy instruction.  Information literacy is the ability to gather relevant information, to process it, to choose the best of it, and to present it in a new format to a selected audience.  Assessment of library information literacy instruction has not always been a priority in higher education, but as budgets tighten, universities and colleges are finding it necessary to supply evidence of student learning in order to satisfy financial supporters and accreditation requirements. Appalachian State University in Boone is one of the sixteen institutions of higher education in the North Carolina State Educational System. As available information sources proliferate, undergraduates are finding it increasingly difficult to keep up with new innovations in the modes of the delivery of information and to live up to the expectations of academia for research papers and projects.  This paper enumerates specific strategies that librarians in the Information Literacy Instruction Program at Belk Library and Information Commons are using to take the lead in the qualitative and quantitative measurement of student learning outcomes on the campus of Appalachian State University. Tools for the measurement of data for assessment are suggested, and there is a discussion of possible methodologies of incorporating information literacy instruction and assessment of student learning into the curricula of academic institutions. Information literacy librarians teach students skills for a life-long learning experience. They are passionate about the need for incorporating information literacy instruction and assessment of student learning into the curricula of academic institutions and have devised methods to measure the student learning outcomes of their information literacy instruction.